2016
DOI: 10.4103/0976-237x.177100
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric changes in pharyngeal airway in Class II division 1 patients treated with Forsus-fixed functional appliance: A three-dimensional cone-beam computed tomography study

Abstract: Objective:Recent years have witnessed a renewed interest to determine a quantifiable relationship between mandibular advancement performed with an orthodontic appliance and the resulting airway volume. The study was conducted to evaluate the volumetric changes in pharyngeal airway space using cone-beam computed tomography (CBCT) in Class II division 1 patients with retrognathic mandible treated by Forsus-fixed functional appliance and to compare them with their pretreatment findings.Materials and Methods:Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
2
9
1
1
Order By: Relevance
“…More recent studies assessed the effects on the pharyngeal airways of several functional appliances, both fixed and removable. [20][21][22][23] The results of these studies were mostly similar to the data reported in the systematic reviews and showed that, in the three-dimensional evaluation of the pharyngeal airway, both fixed 20,21 and removable appliances 22 are effective in increasing airway dimensions, above all at the oropharyngeal level. A study that used magnetic resonance for the evaluation of the upper airways, instead, found no effects of both Twin Block and Herbst appliance.…”
Section: Introductionsupporting
confidence: 80%
“…More recent studies assessed the effects on the pharyngeal airways of several functional appliances, both fixed and removable. [20][21][22][23] The results of these studies were mostly similar to the data reported in the systematic reviews and showed that, in the three-dimensional evaluation of the pharyngeal airway, both fixed 20,21 and removable appliances 22 are effective in increasing airway dimensions, above all at the oropharyngeal level. A study that used magnetic resonance for the evaluation of the upper airways, instead, found no effects of both Twin Block and Herbst appliance.…”
Section: Introductionsupporting
confidence: 80%
“…Among all the studies, airway volume immediately after the treatment was compared with the pretreatment values, we conclude the effects on long-term changes could not explore the effect on long-term changes. The studies varied in the type of appliances used: Oliveira et al [39] used Herbst appliance, Temani et al [40] studied on Forsus, and Alhammadi et al [41] compared removable twin block and Forsus with the control group. All studies reported a significant improvement in the upper airway except for the Forsus group in the study by Alhammadi et al [41] in which insignificant changes were noticed.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis by Xiang et al [20] concluded that functional appliance do produce positive changes especially in oropharyngeal region (PAS) by anterior bodily translation of mandible rather than influencing the growth of mandible. To explain the effects of FFA on airway more precisely Temani et al [21] evaluated the volumetric changes following fixed functional treatment in skeletal Class II case. Study concluded that there was a definite increase in pharyngeal airway space especially in the oropharynx which may prevent developing OSA.…”
Section: Discussionmentioning
confidence: 99%